China Precision Nutrition and Health-KAP Real World Study (CPN-KAPS): rationale, study design, and protocol. Issue 3 (12th December 2022) - Shi, Hanping; Li, Jianping; Mao, Chen; Wang, Binyan; Qin, Xianhui; Bao, Huihui; Wang, Kunhua; Ling, Wenhua; Sun, Guifan; Yang, Jingang; Li, Zengning; Shen, Xian; et al.
Abstract : Background: The burden of chronic diseases and associated morbidities and mortalities are rapidly rising in China. Nutrition and lifestyle are major contributors. Currently, there is a paucity of strong evidence to guide optimal intake of macronutrients and micronutrients for primordial, primary, and secondary prevention of chronic diseases among diverse populations and across life stages in China. Evidence is also lacking on the KAP (Knowledge, Attitude, and Practice) in Chinese populations to inform effective behavior interventions. The China Precision Nutrition and Health-KAP Real World Study (CPN-KAPS) intends to establish a cohort and conduct research in real-world settings to improve KAP and advance precision nutrition. Methods: The CPN-KAPS is a long-term, multicenter, prospective, observational, real-world study that will enroll at least a million adults who meet the inclusion criteria. Each participant will be expected to attend at least 5 follow-up visits (once a year). The primary endpoints include nutritional status and the occurrence, progression, and prognosis of numerous chronic diseases such as cardiovascular and cerebrovascular disease, tumors, chronic kidney disease, Alzheimer's disease, digestive system diseases, diabetes, mortality, and results of the health KAP survey. Secondary endpoints include malnutrition and changes in various chronic disease-related biomarkers and pharmacoeconomic indicators. Results: The CPN-KAPS is still in a formative stage, but we anticipate this study will establish a rich database and biorepository. These resources will create enormous opportunities for scientific discoveries and clinical public health translation. Conclusion: This large-scale, observational, prospective and real-world research will be of great significance and value for an in-depth understanding of China's nutrition and health status, to provide precision nutrition intervention strategy for the prevention and treatment of chronic diseases in Chinese Population.